Impact of Obstetric Communication on Decision-to-Delivery Time - Crimmins, Sarah; Baumer, Sarah; Theodoru, Andrea; Driscoll, Colleen H. (American Journal of Perinatology, 2022)
Objective In obstetric emergencies, care coordination is critical in achieving a “decision-to-delivery” time of 30 minutes. Reliable communication is essential to optimize coordinated care of mother and baby. Clinical mobility (CM) platforms have been shown to improve communication during medical emergencies; however, their impact on improving decision-to-delivery times has not been shown. This study aimed to determine the impact of a new CM platform on decision-to-delivery time.Study Design A multidisciplinary team designed a CM platform that employs a wall-mounted panel paired with mobile technology to alert all relevant clinical staff. This new platform uses in-room preprogrammed messages that alert predetermined responders matching the emergency. For example, the “STAT section” button summons doctors (obstetrics, anesthesiology, and neonatology), obstetric nurses, and newborn resuscitation staff via smartphones. Impact of this platform was assessed with process and outcome data: cord artery pH, 5-minute Apgar's score; and decision for cesarean section to time of: skin incision, uterine incision, and delivery. This pre- and postimplementation study (October–September 2018 vs. January–December 2019) centered on the opening of our new Obstetric Care Unit. Data were analyzed with Chi-square and Mann–Whitney U-test.Results Emergent cesarean delivery was performed in 172 women pre- and 124 postimplementation of the new CM platform. In postimplementation, we observed a 7.4-minute reduction in time from decision-to-delivery (26 pre- vs. 18.6 minutes postimplementation, p = 0.001). Delivery within 30 minutes improved by 15.2% (p = 0.018). Times to skin and uterine incision were also significantly reduced. The two groups had similar neonatal outcomes: birth weight, Apgar's score at 5 minutes, and cord artery pH did not differ, but the study was underpowered to compare these outcomes.Conclusion This new CM platform significantly reduced decision-to-delivery time, in turn improving compliance with the “30-minute rule.” All relevant personnel were contacted specifically, while avoiding overhead paging and other unnecessary messages.Key Points
Keywords: obstetrical communication; decision-to-delivery; cesarean section; clinical mobility